Clinical Characteristics of Temporal Bone Metastases - Kunho Song; Ki-Wan Park; Jae-Hyung Heo; Ik-Chan Song; Yong-Ho Park; Jin Woong Choi (Clinical and Experimental Otorhinolaryngology, 2019)
Objectives The purposes of this study were to evaluate the clinical characteristics of temporal bone metastasis (TBM) and to determine whether the characteristics differed according to primary malignancy. Methods We retrospectively analyzed data on 20 patients diagnosed with TBM between January 2000 and January 2017. Demographics, the period from diagnosis of primary malignancy to TBM diagnosis, the period from TBM diagnosis to death, the type and staging of primary malignancy, otologic manifestations, and TBM sites were assessed. After the primary malignancies were divided into solid cancers and hematologic malignancies, each parameter was compared between the two groups. Results The most common primary malignancy with TBM was lung cancer (45%). The most common otologic symptoms and signs were facial palsy (30.5%) and hearing loss (30.5%). The temporal squama (23%) and the facial nerve (20%) were the most commonly involved. Most TBMs occurred late in the disease process after the primary malignancy first metastasized to other organs. Hematologic malignancies metastasized significantly more frequently to the external auditory canal and the middle ear/mastoid compared to solid cancers (P=0.001 and P=0.004, respectively). Conclusion If otologic manifestations such as facial palsy and hearing loss are presented in patients at advanced stages of malignancy, TBM of primary malignancy should be suspected. In addition, hematologic malignancies tend to metastasize to the external auditory canal and the middle ear cleft more commonly than solid cancers do.